Distribution of Secretion Systems in the Genus Legionella and Its Correlation with Pathogenicity - Qin, Tian; Zhou, Haijian; Ren, Hongyu; Liu, Wenbin (Frontiers in Microbiology, 2017)
The genus Legionella comprises over 60 species, which are important human pathogens. Secretion systems in Legionella pneumophila have been studied extensively because of the essential role of protein secretion in bacterial infection. However, there are few reports describing the secretion systems in non-L. pneumophila species. In this study, we analysed the distribution of secretion systems in L. pneumophila and 18 species of non-L. pneumophila based on whole genome sequences. A total of 74 whole genome sequences from 19 species of Legionella were analysed. Type II and IVB secretion systems were detected in all Legionella strains, but the type I secretion systems was restricted to L. pneumophila. The type IVA secretion system was randomly distributed among different species. Furthermore, we found the type VI secretion system in three non-L. pneumophila strains (Legionella cherrii DSM 19213, Legionella dumoffii Tex-KL, and Legionella gormanii ATCC 33297). In population structure analysis, L. pneumophila formed a conservative cluster and was located at the terminal of the evolutionary tree. At the same time, L. pneumophila, especially eight clone groups (named MCGG1-MCGG8), showed higher intracellular growth ability than non-L. pneumophila species. These results suggest that L. pneumophila has acquired additional secretion systems during evolution, resulting in increased pathogenicity.